A note on Khilnani and TSE's USA algorithm - Marcotte, Patrice (Journal of economic dynamics & control, 1987)
We present a modification of algorithm USA of Khilnani and Tse which is guaranteed to converge to the unique equilibrium solution from an arbitrary starting point.